To be or not to be? A missional and practical theological perspective on being Church without walls amidst coronavirus disease 2019: A challenge or an opportunity? - Beukes, Jacques W. (HTS teologiese studies, 2020)
The novel coronavirus disease 2019 (COVID-19) continues to spread globally. The World Health Organization has declared the outbreak to be a global pandemic. Millions of people have been diagnosed globally; and at the time of publishing this article, more than a million people died because of the virus. South Africa reported its first official COVID-19 case on 05 March 2020, and since then the figures dramatically increased. On 15 March 2020 and the week thereafter on 23 March 2020, South Africans were waiting in anticipation as they learned from various (social) media platforms that the President would make a crucial announcement regarding the impact of COVID-19 and the drastic effect it will have on their country. Immediately drastic and tremendous measures were announced to safeguard South Africans and to contain the spread of the virus that was impacting communities of all faiths. Does this situation of crisis and global pandemic pose a challenge or a new opportunity for the church to be church with integrity? This article explores this question by engaging with the missional and practical theological perspectives such as the church being missional, relevant and contextual. This situation both challenges and provides opportunities to revisit and redefine being church outside the traditional walls of the church as missional describes being a missionary everywhere you are. This article engages with the missional perspective that the church is called to be church everywhere as well as being church in a time of the fourth industrial revolution.Contribution: This research challenges the traditional discourse and believers’ current understanding and praxis of being church. This research invites the church to embrace new (old forgotten) ways of being church because of a medical global pandemic (health sciences). It brings together insights from missional ecclesiology and practical theology and engages with social and human sciences.